Experimental Investigation on Factors Affecting Oil Recovery Efficiency during Solvent Flooding in Low Viscosity Oil Using Five-Spot Glass Micromodel - Hematpur, Hamed; Davani, Mohammad Parvaz; Safari, Mohsen (Journal of Petroleum Research and Studies, 2014)
Lack of experimental study on the recovery of solvent flooding in low viscosity oil is obvious in previous works. This study concerns the experimental investigation on oil recovery efficiency during solvent/co-solvent flooding in low viscosity oil sample from an Iranian reservoir. Two micromodel patterns with triangular and hexagonal pore structures were designed and used in the experiments. A series of solvent flooding experiments were conducted on the two patterns that were initially saturated with crude oil sample. The oil recovery efficiency as a function injected pore volume was determined from analysis of continuously captured pictures. Condensate and n-hexane were employed as base solvents, and Methyl Ethyl Ketone (MEK) and Ethylene Glycol Mono Butyl Ether (EGMBE) used as co-solvents. The results revealed that not only does the solvent flooding increase the recovery in low viscosity oil but also this increase is evidently higher with respect to viscous oil. But, type of solvent or adding co-solvent to solvent does not noticeably increase the recovery of low viscosity oil. In addition, further experiments showed that presence of connate water or increasing injection rate reduces the recovery whereas increasing permeability improves the recovery. The results of this study are helpful to better understand the application of solvent flooding in low viscosity oil reservoirs.